Precision, efficiency and cost of shapes of fixed area plots for plantation ages of Pinus taeda L. in Santa Catarina State - Zator Filho, Alois; Minatti, Myrcia; Woycikievicz, Antonio Pedro Fragoso; Trautenmuller, Jonathan William; Nakajima, Nelson Yoshihiro (Scientia Agraria Paranaensis, 2020)
Generally, the forest populations are extensive and frequently require to be inventoried in short term, where the implementation of forest inventory is closely linked to the sampling theory. With objective to compare three different shapes of fixed area plots to estimate parameters of the forest as average diameter, basal area, the number of trees and volume per hectare, evaluating the respective precision, relative efficiency, cost and measurement time in four different ages. The rectangular plot had presented better precision to estimate the average DBH, number of trees and basal area and the circular plot with better precision for volume per hectare. About efficiency, the square plot had presented the best efficiency for the variable average DBH, basal area and volume and the circular plot was the most efficient for the numbers of trees ha-1. The square plot also had shown the lower cost and measurement time to estimate the variables evaluated. The rectangular plot had presented the best precision in the estimative of the variables, as well as, the lower sampling error in the most of the cases evaluated in this study, following the circular plot, and the square plot with lower precision. In relation to the efficiency, the square plot had presented the best performance and the rectangular plot the worst performance in all age classes and evaluated variables. The square plots as the best plot shape to estimate the variables average DBH, number of trees, basal area and volume per hectare.